Environmental Economics and Sustainable Development: A Study on Environment Management Policy of Nepal - Kharel, Khom Raj (Journal of Development Review, 2020)
Environmental economics has important contributions to the understanding of environmental phenomena, their causes, effects, and possible solutions that have been developed from various areas of economic theory and original applications and developments. Economists are to provide an increasingly effective contribution to the study of environmental issues and the pursuit of sustainable development. In particular, empirical analyses are of fundamental importance both to environmental economics and to the sustainability debate. The objective of this study is to analyze the environmental problems which are being encountered as a result of attempts to produce economic development in the nation. Descriptive research design and descriptive statistics have been followed to make an analysis. The secondary information was collected. It was found that the acts and regulations related to the environment have not been effective due to the lack of integrated environmental policy, lack of coordination among various agencies, and lack of adoption of a holistic approach.